Self-adaptive channel allocation in asymmetry network - Ke, Shan. (2008)
This thesis study and survey the Asymmetrical Digital Subscriber Loop (ADSL)'s technology, the new market requirement, and the current relative technology development. Based on these, a powerful algorithm for asymmetry netqork is proposed.